2014
DOI: 10.4172/2157-7110.1000308
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Safety of Strawberries and Lettuce for Domestic Consumption in Egypt

Abstract: Food borne outbreaks with fresh produce are increasingly being reported in developed countries. Food borne illness is an important threat for human health also in developing countries, but data on food safety, in particular related to microbial food safety in fruits and vegetables, the developing world are scarce. In the present study, the sanitary quality and safety of Egyptian lettuce and strawberries, obtained from either primary production or domestic retail market, was assessed by enumeration of faecal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
1
10
1
Order By: Relevance
“…The overall prevalence rate (5.3%) observed in the present study is higher than what has been generally reported from previous studies in the developed world (Duffy et al, 2005;Castillo et al, 2004;Giusti et al, 2010;Gorski et al, 2011;Johnston et al, 2005;Micallef et al, 2012., Mukherjee et al, 2006, but comparatively lower than that reported in some other developing countries (Abakpa et al, 2015;Ndiaye et al, 2011;Uyttendaele et al, 2014). …”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The overall prevalence rate (5.3%) observed in the present study is higher than what has been generally reported from previous studies in the developed world (Duffy et al, 2005;Castillo et al, 2004;Giusti et al, 2010;Gorski et al, 2011;Johnston et al, 2005;Micallef et al, 2012., Mukherjee et al, 2006, but comparatively lower than that reported in some other developing countries (Abakpa et al, 2015;Ndiaye et al, 2011;Uyttendaele et al, 2014). …”
Section: Discussioncontrasting
confidence: 75%
“…According to a study by Uyttendaele et al (2014), good agricultural practices (GAP) are well understood and implemented in developed countries but not so in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…The MENA countries bordering Europe are in a prime location to export produce to the EU. However, unfortunately, most food control systems in the MENA region are unable to meet the mandated international requirements, due to lack of the required advanced technical and scientific knowledge, political will, and to an unacceptable level of food safety by small-scale farmers and the domestic market [73]. This remains largely unaddressed, despite major reforms being introduced to their national food safety systems, with varying degrees of accomplishments.…”
Section: The Current Status Of Food Safety In Developing Countriesmentioning
confidence: 99%
“…Studies reporting on food safety issues in developing countries are very few, but what exists indicates there is widespread contaminated soil; poor agricultural growing methods with the misuse of pesticides, hormones, and fertilizers; and inappropriate post-harvest practices along the food chain, such as the use of untreated wastewater for irrigation and the processing of vegetables [37,73,93,94,95]. The unregulated use of feces-contaminated water for irrigation and the application of untreated manure on fields are classified as primary risk factors; these are largely practiced in Egypt and Lebanon, leading to contamination of the agricultural environment and fresh produce [37,73].…”
Section: The Current Status Of Food Safety In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation